Antimicrobial Properties of Mesenchymal Stem Cells: Therapeutic Potential for Cystic Fibrosis Infection, and Treatment - Morgan T. Sutton; David Fletcher; Santosh K. Ghosh; Aaron Weinberg; Rolf van Heeckeren; Sukhmani Kaur; Zhina Sadeghi; Adonis Hijaz; Jane Reese; Hillard M. Lazarus; Donald P. Lennon; Arnold I. Caplan; et al. (Stem Cells International)
Cystic fibrosis (CF) is a genetic disease in which the battle between pulmonary infection and inflammation becomes the major cause of morbidity and mortality. We have previously shown that human MSCs (hMSCs) decrease inflammation and infection in the in vivo murine model of CF. The studies in this paper focus on the specificity of the hMSC antimicrobial effectiveness using Pseudomonas aeruginosa (gram negative bacteria) and Staphylococcus aureus (gram positive bacteria). Our studies show that hMSCs secrete bioactive molecules which are antimicrobial in vitro against Pseudomonas aeruginosa, Staphylococcus aureus, and Streptococcus pneumonia, impacting the rate of bacterial growth and transition into colony forming units regardless of the pathogen. Further, we show that the hMSCs have the capacity to enhance antibiotic sensitivity, improving the capacity to kill bacteria. We present data which suggests that the antimicrobial effectiveness is associated with the capacity to slow bacterial growth and the ability of the hMSCs to secrete the antimicrobial peptide LL-37. Lastly, our studies demonstrate that the tissue origin of the hMSCs (bone marrow or adipose tissue derived), the presence of functional cystic fibrosis transmembrane conductance regulator (CFTR: human, Cftr: mouse) activity, and response to effector cytokines can impact both hMSC phenotype and antimicrobial potency and efficacy. These studies demonstrate, the unique capacity of the hMSCs to manage different pathogens and the significance of their phenotype in both the antimicrobial and antibiotic enhancing activities.